Development of Jetty Structure Design Procedures at The Schematic Design Stage with The Implementation of Computational Design and Building Information Modelling to Improve Design Time Performance - Fitriansyah, Aidil; Latief, Yusuf (UI Scholars Hub, 2024)
The construction sector faces persistent productivity challenges, significantly hindering the efficiency of design workflows. Computational Design (CD) and Building Information Modeling (BIM) offer potential solutions. CD enables the exploration of parametric design alternatives, while BIM enhances collaboration, visualization, and decision-making through comprehensive 3D models. This study aimed to investigate the processes and activities involved in the structural design of jetties during the schematic design phase using CD and BIM and to assess the impact of these activities on design time performance. A comprehensive analysis of secondary data was carried out, interviews were conducted with design experts, and quantitative analysis using SPSS29 was employed to assess the impact of the design procedures on design time performance. The investigation identified nine critical business processes in the structural jetty design using CD and BIM, comprising 37 design activities. The impact assessment revealed two crucial factors, CD-BIM Design Activities, and Internal Design Review, showing that incorporating computational design and BIM processes into structural design procedures significantly improved design time performance. The research highlights the transformative role of CD and BIM in streamlining structural design processes, marking a significant advancement in the pursuit of efficiency within the civil engineering sector.